Two new triterpenoids from the stems of Celastrus orbiculatus Thunb. (October 2018) - Wang, Lun; Tang, Huan; Chen, Kai; Xue, Lin-Lin; Ye, Hao-Yu; Ma, Li-Fang; Li, Zi-Yuan
Graphical abstract: Highlights: Two new triterpenes were isolated from the Celastrus orbiculatus . The structures were elucidated by NMR spectroscopic and MS methods. Compounds1 showed weak anti-inflammatory activities. Abstract: Two new triterpenoids, named as 3 β -( E )- p -caffeoylnepeticin (1 ) and 3 β -( E )-3, 4-dimethoxycinnamate-20( S )-dammarenediol II (2 ), along with three known compounds3, 4 and5 were isolated from the stems of Celastrus orbiculatus Thunb. The structures of these compounds were elucidated by spectroscopic methods including IR, 1D and 2D NMR as well as by high-resolution mass spectrometric analysis. The anti-inflammatory activities and the cytotoxic effects were evaluated on lipopolysaccharide induced nitric oxide production in RAW 264.7 cells and two tumor cell lines (MCF-7 and A2780s), respectively. Results showed that compounds1 and3 exhibited weak anti-inflammatory activity with the IC50 value of 18.50 and 10.51 μM respectively, while all compounds were inactive in both cell lines (IC50 > 20 μM).